Zalacca secunda - a Stemless Rattan Palm from Arunachal Pradesh - Thomas, Sunny; Haridasan, K.; Borthakur, S. K. (Indian Forester, 1999)
Zalacca secunda - a stemless Rattan was located during a taxonomic survey from the eastern part of Arunachal Pradesh. The paper describes the characteristic features of the genus Zalacca and the species Z. secunda from Arunachal Pradesh.